Tax-benefit microsimulation modelling in Zambia: A feasibility study - Mari Kangasniemi; Helen Barnes; Gemma Wright; Michell Mpike (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This study presents the findings from a feasibility study on the potential for developing a static tax-benefit microsimulation model for Zambia. The paper focuses on the details of the tax-benefit system and possible data sources, building on information collected in the initial scoping study of all countries in the Southern African Development Community and East African Community. The paper concludes with an assessment of the feasibility of producing a tax-benefit microsimulation model and its potential sustainability into the future.
Keywords: E62; H24; 330; tax; benefits; microsimulations; revenue